The influence of the experimental composition of disinfection preparations based on polyhexamethyleneguanidine and nanoaquachelates of metals on test cultures of microorganisms - I. V. Romazan; I. B. Turko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
When developing a new and effective disinfectant, the existing microbial composition and the ability of microorganisms to form biofilms should be considered. Bacteria in the environment on various surfaces exist in two forms: in the form of planktonic cultures and the form of a formed microbial biofilm. Microorganisms in biofilm are more resistant to factors existing in nature and to the action of various antibacterial compounds. Therefore, when developing disinfectants, it is essential to study the bactericidal effect of newly created agents on bacteria that have formed biofilms. The purpose of the work was to investigate the effect of an experimental composition of a disinfectant based on polyhexamethyleneguanidine (PHMG) and nanoaquachelates of metals on the biofilm-forming properties of microorganisms and to determine the antimicrobial effect of the agent applied to test materials (stainless and galvanized steel, wood, tile). Microbiological studies on the determination of the bactericidal effect of experimental variants of the disinfectant with PHMG and nanoaquachelates of metals were carried out following generally accepted methods. Research on the effect of different disinfectant concentrations on microorganisms in biofilms was carried out according to the methodological recommendations “Determining the bactericidal activity of disinfectants on bacteria in biofilms”. All studies were carried out in triplicate, and the obtained data were subjected to statistical processing. The use of a 2 % solution of the developed disinfectant based on nanoaquachelates of metals and PHMG with an exposure of 40 minutes provides an entirely bactericidal effect on the test cultures of S. aureus, E. coli, and C. albicans in the biofilm. When studying the bactericidal activity of the research composition of the developed disinfectant against museum strains of microorganisms applied to the test materials, it was established that: when using the museum strain of S. aureus applied to galvanized and stainless steel to ensure the bactericidal effect, a concentration of 0.0625 % and 0.0312 % is required for exposures of 20 and 40 minutes. When using wooden and tiled surfaces, a higher concentration of disinfectant is needed, namely 0.125 % and 0.0625 %, for exposures of 20 and 40 minutes; for contamination by the museum strain of E. coli of galvanized and stainless steel, the bactericidal effect was observed at a concentration of 0.0312 % for both 20 min and 40 min. To achieve the bactericidal effect of the agent on a wooden surface within 20 minutes of action, the required concentration of the agent was at least 0.125 %, and after exposure for 40 minutes – 0.0625 %. The bactericidal effect on the tile surface was provided at concentrations of 0.0625 % and 0.0312 % for 20 and 40 min of exposure, respectively; when using the museum strain of C. albicans applied to metal surfaces, the bactericidal effect was observed at disinfectant concentrations of 0.0625 % and 0.0312 % and exposure for 20 and 40 minutes. The tiled surface was disinfected from C. albicans at a composition concentration of 0.0625 % within 20 minutes of exposure, and a wooden surface was disinfected at a composition concentration of 0.125 %.